PENGARUH KEPEMIMPINAN DIREKTUR TERHADAP KUALITAS PELAYANAN PUBLIK DI RUMAH SAKIT UMUM DAERAH (RSUD) DOKTER RUBINI MEMPAWAH - Ifa Yudha Putri E.42009011 (FISIP Universitas Tanjungpura Pontianak, 2013)
This thesis entitled “Director Leadership Influence on the Quality of Public Services at the Regional General Hospital (Hospital) Dr. Rubini Mempawah”.This thesis aims to determine the effect of leadership on the quality of public services director at Doctors Hospital Rubini Mempawah. This research was chosen because the author saw no problems related to the quality ofpublic services in the Doctors Hospital Rubini Mempawah. Obviously a lot of factors that affect the quality of service, in this study this study the researchers suspect that the leadership of a good director will produce the quality of public services and to give satisfaction to the people who feel the service.This research is quantitative research to test the hypotheses. The population in this study in the field of physician services in hospitals Rubini Mempawah with a population of as many as 157 employees. Samples in this study amounted to 61 respondents using proportionate stratified random sampling technique. Data processing techniques using a questionnaire and has been tested with test validity and reliability. The data analysis technique used is the analysis of product moment and continued with determinant coefficient determines the magnitude of the effect between the two variables. The conclusion of this study is the director of leadership has a significant effect on the quality of public services by 19.8%. That is, the quality of service will increase if the director is done with good leadership, so that employees can provide services to the community because according to the directives of the Director. For the remaining 80.2% is influenced by other variables not examined in this study suchas: employee motivation, employee skills, wquipment and facilities.Keywords: Leadership Director, Quality Public Services and Hospital Dr. Rubini Mempawah